Estimation of treatment effects under combined sampling and experimental designs - Smith, Christina D. (Kansas State University, 2007)
Over the years sampling and experimental design have developed independently with little mutual compatibility. However, many studies do (or should) involve both a sampling design and an experimental design. For example, a polluted site may be exhaustively partitioned into area plots, a random sample of plots selected, and the selected plots randomly assigned to three clean-up regimens. In this research the relationship between sampling design and experimental design is discussed and a basic review of each is given. An estimator that combines sampling and experimental design is presented and it's development explained. Properties of this estimator will be derived and some applications of the estimator will be examined. Finally, a simulation study comparing this estimator with the traditional estimator will be presented.
Keywords: Sampling design; Experimental design; Combined estimation; Horvitz-Thompson estimation; Treatment effect; Statistics (0463)